Gene-environment and Gene-gene Interaction in the Determination of Plasma Homocysteine Levels in Healthy Middle-aged Men - Dekou, Vanessa; Gudnason, Vilmundur; Hawe, Emma; Miller, George J.; Stansbie, David; Humphries, Steve E. (Thrombosis and Haemostasis, 2001)
Healthy middle-aged men (n = 1470) from eight general practices across Britain were examined for plasma total homocysteine levels and genotyped for the A222V polymorphism in the methylene-tetrahydrofolate (MTHFR) gene, the 68 bp insertion polymorphism in exon 8 of the cystathionine b synthase (CBS) gene and the D919G polymorphism in the methionine synthase (MS) gene. The median value for plasma homocysteine was 11.90 μmol/l (25–75% Interquartile range 10.10-14.20) for the whole sample. Smokers had significantly higher homocysteine levels than non-smokers (12.90 vs 11.70 μmol/l and p <0.00005) and levels significantly differed according to folate (p-value <0.00005), with men in the lowest quartile of folate having the highest median homocysteine levels. Genotype at all three loci was associated with differences in plasma homocysteine level. Individuals homozygous for the MTHFR V222 allele had 1.6 μmol/l higher median homocysteine levels when compared to the other two genotypes (p <0.00005), while for the CBS and MS genes, individuals carrying one or more of the rare alleles had lower median homocysteine than individuals homozygous for the common allele (0.80 μmol/l, p <0.03, and 0.70 μmol/l, p <0.04 respectively). The raising effect associated with homozygosity for the V222 allele was greater in men in the lowest quartile of folate (interaction between folate and genotype p = 0.02), but none of the genotype effects was significantly modulated by B12 levels. While the raising effects of V222 and MS D919 homozygosity on homocysteine level were essentially additive, the homocysteine lowering effect associated with the CBS 68bp allele was seen most strongly in men homozygous for the V222 allele (MTHFR-CBS genotype interaction p = 0.03) and the D919 allele (MS-CBS interaction p = 0.09). Age, folate, B12 and smoking explained 13.48% of the variance while the three genotypes combined and with interaction terms explained only an additional 2.63%. This interaction between CBS genotype and MTHFR and MS genotype points to a key role of the CBS transulphuration pathway in the metabolism of homocysteine that may be particularly important as a compensatory mechanism in subjects with low dietary folate.
Keywords: MTHFR; CBS; methionine synthase; homocysteine; folate